10 Tips for Choosing Your University -- SMU Infographics - Singapore Management University (Institutional Knowledge at Singapore Management University, 2014)
We know the process of choosing the right university can be overwhelming and challenging as you sift through voluminous information and try to answer all those questions popping inside your head. So we’ve come up with a list to help you make that all-important decision! Download this infographic to find out what are the top 10 considerations you should make before making the life-changing decision!